Controllable thermal expansion in ferroelectric ceramics through two-dimensional periodically orthogonal poling. (15th January 2021) - Wang, Qiangzhong; Li, Faxin
Abstract: Controlling the thermal expansion coefficient can effectively reduce the thermal stress and enhance the reliability of materials or structures. In this work, based on the fact that the thermal expansion coefficient of ferroelectric ceramics is negative along the poling direction and positive along the transversal direction, we tailored the domain structure of Lead Zirconate Titanate (PZT) ceramics by two-dimensional periodically orthogonal poling. The in-plane thermal expansion coefficient can be controlled in a wide range ( α = − 8.2 × 10 − 6 ∘ C − 1 ∼ 2.5 × 10 − 6 ∘ C − 1 ) which may find wide applications in the fields of thin film fabrication, electronic packaging, etc. Graphical abstract: Image, graphical abstract